The first biography of Jesus: genre and meaning in Mark's gospel - Bond, Helen K. (William B. Eerdmans Publishing Company, 2020)
"Argues that Mark's author used the genre of biography to extend the gospel from an earlier narrow focus on the death and resurrection of Jesus so that it included the way of life of its founding figure"